Approximate Controllability of a 3D Nonlinear Stochastic Wave Equation - Peng Gao (Journal of Applied Mathematics)
We study the well-posedness of a 3D nonlinear stochastic wave equation which derives from the Maxwell system by the Galerkin method. Then we study the approximate controllability of this system by the Hilbert uniqueness method.